24-Hour Carotid Stent Patency and Outcomes After Endovascular Therapy: A Multicenter Study. Issue 1 (27th December 2022) - Allard, Julien; Delvoye, François; Pop, Raoul; Labreuche, Julien; Maier, Benjamin; Marnat, Gaultier; Sibon, Igor; Zhu, François; Lapergue, Bertrand; Consoli, Arturo; Spelle, Laurent; Denier, Christian; et al.
Abstract : Background: Management of extracranial internal carotid artery steno-occlusive lesion during endovascular therapy remains debated. Stent occlusion within 24 hours of endovascular therapy is a frequent event after acute carotid artery stenting, and we currently lack large population results. We investigated the incidence, predictors, and clinical impact of stent occlusion after acute carotid artery stenting in current clinical practice. Methods: Patients treated by endovascular therapy with acute carotid artery stenting between 2015 and 2019 in 5 large-volume endovascular-capable centers were retrospectively analyzed. Patients were separated in 2 groups according to the stent patency at 24 hours after carotid artery stenting. We compared baseline characteristics, treatment modalities, and clinical outcome depending on 24-hour stent patency. Primary end point was favorable outcome, defined as a modified Rankin Scale score 0–2 at 3 months. Results: A stent occlusion was observed in 47/225 patients (20.9%). Patients with stent patency had a lower baseline National Institutes of Health Stroke Scale (median [interquartile range]: 13 [7–17] versus 18 [12–21]) and had more often stroke of atherothrombotic origin (77.0% versus 53.2%). A higher stent patency rate was found for patients treated with P2Y12 antagonists at the acute phase (odds ratio [OR]‚ 2.95 [95% CI‚ 1.10–7.91]; P =0.026) and treated with angioplasty (OR‚ 2.42 [95% CI‚ 1.24–4.67]; P =0.008). A better intracranial angiographic reperfusion was observed in patients with 24-hour stent patency compared with patients without stent patency (OR‚ 8.38 [95% CI‚ 3.07–22.78]; P <0.001). Patients with a stent patency at 24 hours had a higher chance of favorable outcome (OR‚ 3.29 [95% CI, 1.66–6.52]; P <0.001) and a lower risk of death (OR‚ 0.32 [95% CI, 0.13–0.76]; P =0.009). Conclusions: One out of 5 patients treated with carotid artery stenting during endovascular therapy presented a stent occlusion within 24 hours. This event was associated with worse functional outcome. Stroke etiology, P2Y12 antagonist administration, quality of intracranial reperfusion, and angioplasty were associated with 24-hour stent patency.